Takotsubo syndrome and COVID‐19: A systematic review - Hoomaan Ghasemi; Sina Kazemian; Seyed Aria Nejadghaderi; Mahan Shafie (Health Science Reports, 2023)
Abstract Background and Aims Takotsubo syndrome (TTS), also known as stress cardiomyopathy, is characterized by acute and transient left ventricular dysfunction and has increased during the COVID‐19 pandemic. Herein, we aim to review studies on TTS that were associated with COVID‐19 infection, vaccine, and other COVID‐19‐related etiologies including psychosocial stressors. Methods We systematically searched PubMed, EMBASE, and Scopus up to May 12, 2022. We included case reports, case series, and original articles that reported at least one TTS case associated with COVID‐19, or TTS cases after receiving COVID‐19 vaccines, or TTS cases secondary to psychological stress due to the COVID‐19 pandemic. The quality assessment was conducted using the Joanna Briggs Institute checklist. Results Sixty‐seven articles including 102 cases were included. Hypertension was the most frequently accompanying comorbidity (N = 67 [65.6%]) and the mean left ventricular ejection fraction was 36.5%. Among COVID‐19 patients, the in‐hospital mortality rate was 33.3%. On the other hand, only one COVID‐19‐negative individual expired (2.3%). The most common presenting clinical symptom was dyspnea in 42 (73.6%) patients. the mean time interval from the first symptom to admission was 7.2 days. The most common chest imaging finding was ground‐glass opacity which was reported in 14 (31.1%) participants. The most common abnormalities were T‐wave inversion in 35 (43.2%) and ST‐segment elevation in 30 (37%). Brain natriuretic peptide and troponin were elevated in 94.7% and 95.9% of participants, respectively. Conclusion The TTS in patients with COVID‐19 is almost rare, whereas it could lead to a great mortality and morbidity. An individual with COVID‐19, especially an elderly woman, presented with dyspnea in addition to a rise in brain natriuretic peptide and troponin should be evaluated for TTS.